Water quality and shellfish related gastrointestinal disease cases in Kota Bharu - Eh Rak, Aweng (2006)
Shellfish or to be specific, the family of freshwater mussels and the species known as Corbicula fluminea or in the local dialect recognized as â€œetakâ€ is one of the food peculiar to Kelantan. â€œEtakâ€ is a filter feeder. Therefore, a lot of pollutants could be accumulated in the â€œetakâ€™sâ€ tissues including pathogenic bacteria which are mainly contributed by improperly treated sewage discharged into the river. Besides direct contamination from the habitats, C. fluminea may also be contaminated during preparation and sale. The objective of this study is to identify the correlation between water quality, shellfish tissue contaminations and the cases of gastrointestinal diseases in Kota Bharu as well as to study the stage of bacteria contamination in the shellfish preparation cycle and to compare the bacteria concentration in river bed and selling points of shellfish. The methodology in this study involves water quality sampling and shellfish sampling, with lab analysis being done by accredited lab and secondary data was obtained from Department of Health, Kota Bharu regarding the cases of gastrointestinal diseases in Kota Bharu. There are two stages of shellfish sampling, the first stage is raw â€œetakâ€ from the river bed and the second stage is process â€œetakâ€. Three sampling stations were chosen. Shellfish tissues were analyzed by bacteriology lab of Fisheries Research Institute located in Batu Maung, Penang and water quality analysis was performed by accredited laboratory. During the study, bacterial contamination in raw C. fluminea or â€œetakâ€ was found to be high and exceeded the standard especially for Escherichia coli and Fecal coliform. Raw C. fluminea was found to be unsafe for consumption. Bacterial contamination in processed C. fluminea or â€œetakâ€ was also found to be high but lesser in concentration as compared to raw one. Bacteria contamination occurred mainly in the river bed although contamination during the selling process is also possible. High concentrations of bacteria in the river result in high concentrations of bacteria in â€œetakâ€ tissues and these could possibly lead to high gastrointestinal diseases in Kelantan, particularly in Kota Bharu.